Structural characteristic and dielectric properties of zirconia toughened alumina - Rejab, N. A. (2020)
Zirconia toughened alumina (ZTA) has shown a great effect in the cutting tool application due to its high hardness and comparable fracture toughness. However, the capability of the materials to be applied in as the dielectric resonator antenna (DRA) is not being discussed in detail. In this study, an attempt is made to further explore the potential of ZTA to be applied in DRA. Various related characterization techniques were applied that is subjected to DRA properties. The addition of CeO2 (0 wt.% to 15 wt.%) on ZTA has been pressed into pellets shape and sintered at 1600 °C for 2 hours under pressureless conditions. Based on the XRD analysis, only corundum and yttria doped zirconia phases were present. Shift in position of the zirconia peaks was observed due to an existence of Ce2Zr3O10 phase. For the DRA measurement, ZTA with 10 wt.% CeO2 addition have resonated at 6.76 GHz which is suitable for X-band applications. Meanwhile the radiation pattern indicated the omnidirectional characteristic, which suggested that the signal could be received by this dielectric antenna in various positions. Therefore, ZTA-10 wt.% CeO2 have high potential to be used as DRA that operates X-band frequency range applications.